Establishing Health Biotech and Enhancing Local Manufacturing of Pharmaceuticals in Sub-Saharan Africa - Taye T Balcha MD, MPH, PhD (SAGE Publishing, 2018)
Although many nations in Sub-Saharan Africa (SSA) have recently recorded impressive economic growth, and several countries could attain middle-income status in the next decade, there is no or little concurrent advance in health biotech with little capabilities for manufacturing of medicines, medical supplies, and health commodities in the region. They import majority of medicines, medical supplies, and health commodities used in national programs including immunization, family planning, tuberculosis, HIV, and malaria that drive health outcomes and population-level impact with supports mainly obtained from high-income countries, multilateral agencies, or philanthropies. Nevertheless, there is a growing global debate that countries should graduate from receiving development assistance which goes to the most important health programs like immunization when nations transition from low-income to middle-income economic status. Since sudden withdrawal of all or partial development assistance could send a shock to the health care and dent the trajectory toward achieving the health Sustainable Development Goal, it is imperative to urgently establish or strengthen health biotech and enhance manufacturing of pharmaceuticals in SSA.